An academic achievements visualization research since the 21st century: research on salvage surgery for head and neck cancer - Zhou, Bo; Cheng, Jingyi; Deng, Kexin (Frontiers in Surgery, 2024)
Background: Head and neck cancer is the 6th most common malignancy worldwide, and its incidence is still on the rise. The salvage surgery has been considered as an important treatment strategy for persistent or recurrent head and neck cancer. Therefore, we conducted a bibliometric analysis of salvage surgery for head and neck cancer since the 21st century. Methods: The literature about salvage surgery of head and neck cancer in Web of Science was searched. CiteSpace and VOSviewer were used to analyze main countries, institutions, authors, journals, subject hotspots, trends, frontiers, etc. Results: A total of 987 papers have been published since the 21st century. These publications were written by 705 authors from 425 institutions in 54 countries. The United States published 311 papers in this field and ranked first. Head & Neck was the most widely published journal. The main keyword clustering included terms such as #0 stereotactic radiotherapy (2012); #1 randomized multicenter (2007); #2 salvage surgery (2004); #3 functional outcomes (2014); #4 transoral robotic surgery (2013); #5 neck high-resolution computed tomography (2010); #6 complications (2008); #7 image guidance (2019). The current research frontiers that have been sustained are "recurrent", "risk factors", and "reirradiation". Conclusion: The current situation of the salvage surgery for head and neck cancer in clinical treatments and basic scientific research were summarized, providing new perspectives for the development of salvage surgery for head and neck cancer in the future.